THE ROLE OF ENDORPHIN HORMONES AS PREDICTORS OF PREGNANCY ANXIETY - Putriatri Krimasusini Senudin; Saidah Syamsuddin; Andi Armyn Nurdin (International Journal of Nursing and Health Services (IJNHS), 2019)
Pregnancy anxiety is a common problem with a prevalence of 14-54% and is the highest in the third trimester. Pregnancy anxiety is associated with neurotransmitter dysregulation and endocrine changes in the Hypothalamus Pituitary Adrenal (HPA) axis pathway through the increase of synthesis and the release of corticotropin-releasing hormone (CRH), Adrenocorticotropic Hormone (ACTH) and cortisol to suppress endorphin hormone production. This study aims to determine the relationship of endorphin hormone levels to pregnancy anxiety. This study was an observational study using a cross-sectional approach to 57 pregnant women. The anxiety level was measured by using the Hamilton Anxiety Rating Scale (HARS) and the ELISA kit with plasma specimens was employed to examine the endorphin hormone levels. The results showed that endorphin hormone levels acted as predictors of pregnancy anxiety (p = 0,000). Keywords: Anxiety, Pregnancy, Endorphin